418 OVEREXPRESSION OF ESTROGEN RECEPTOR BETA CONTRIBUTES TO EXOGENOUS TESTOSTERONE-INDUCED GERM CELL APOPTOSIS IN RATS. (1st January 2006) - Schwarcz, M. G.; Lue, Y. H.; Pope, V. S.; Ma, K.; Hikim, Sinha A.P.; Wang, C.; Swerdloff, R. S.
Abstract : Understanding the molecular mechanisms of germ cell apoptosis is essential for male contraceptive development and infertility treatment. We have demonstrated that testosterone (T) implant (3 cm) increases germ cell apoptosis exclusively during stages VII-VIII of the seminiferous epithelium cycle. However, the underlying molecular mechanisms of exogenous T-mediated apoptosis remains an interesting and underexplored question. The objective of this study was to examine the role of estrogen receptor beta (ERβ) on exogenous T-induced germ cell apoptosis in rats. Groups of five young adult (60 days old) Sprague-Dawley rats were given either 3 cm T implant or empty Silastic capsule (control) for 4 weeks. Reproductive hormones were assayed by radioimmunoassay. Germ cell apoptosis was detected by TUNEL assay. Western blot and immunohistochemistry were used to examine ERβ expression and localization in the testis. We found that consistent with our previous observations, plasma FSH, LH, and intratesticular T levels were markedly suppressed in the T-treated group when compared to the controls. Suppression of intratesticular T was followed by an increase in germ cell apoptosis exclusively during the androgen-responsive stages VII-VIII. In control rats, ERβ immunostaining was observed in the Leydig cells, preleptotene and pachytene spermatocytes. After T treatment for 4 weeks, ERβ immunoexpression was increased in Leydig cells. Interestingly, we found ERβ immunoexpression was up-regulated in the apoptotic pachytene spermatocytes and round spermatids. In conclusion, the overexpression of ERβ in apoptotic germ cells suggests the involvement of ERβ in the induction of germ cell apoptosis induced by T implantation in rats. Studying ERβ-mediated cell death and survival, pathways may give rise to potential targets for male contraceptive development and infertility intervention.